Analysis of Patch Antenna with Broadband Using Octagon Parasitic Patch - Sun-Woong Kim; Ho-Gyun Yu; Dong-You Choi (Sensors, 2021)
This paper proposes a novel broadband octagonal patch antenna with parasitic patches. The proposed patch antenna is constructed with four parasitic patches around a central radiating octagonal element. It is illustrated that this arrangement can be used to improve the antenna bandwidth and gain when compared with that of conventional antennas. The proposed patch antenna is very simple, low-profile, and economical. The typical analysis of the proposed antenna is analyzed by the S11(S-parameter), the radiation pattern, and the realized gain. It can achieve an impedance bandwidth of 1.44 GHz and a high gain of 8.56 dBi in the 8.5 GHz band. Furthermore, the proposed antenna shows that the directional pattern and HPBW measurement results of E and H-plane were 70° and 74° at 8.5 GHz, and 74° and 83° at 9 GHz, and 47° and 42° at 9.5 GHz, respectively.